Infecções do trato urinário em pacientes adultos internados em UTI de um hospital de ensino no Brasil: etiologia, resistência e fatores de risco - Almeida, Vitelhe Ferreira (2020)
Introduction- Urinary tract infections (UTI) are frequent in critically ill patients, generally associated with the use of indwelling urinary catheter (IDC) leading to significant morbidity. Objective- To evaluate the epidemiology, etiology, risk factors and evolution of urinary tract infections in critically ill adult patients. Material and methods- The retrospective surveillance study (2012-2018) of the incidence of the first episode of UTI in patients admitted to the Adult Intensive Care Unit of a tertiary referral hospital in Brazil. Through systematic screening of patients' medical records, an individual form with epidemiological, clinical and microbiological data was filled out. Intrinsic and extrinsic risk factors were assessed through univariate and multivariate statistical analyzes. In addition, the use density of the following antimicrobials was calculated: cefepime, ceftriaxone, imipenem, meropenem, polymyxin B and tigecycline. The in vitro resistance spectrum was determined by the Hospital's Microbiology Laboratory. Results- In the 7 years of investigation, 363 patients were identified (252 with bacteriuria, 109 with candiduria and 2 episodes of Trichosporon spp.) admitted to ICU with the first episode of UTI-acquired at the Unit, based on microbiological criteria. The incidence of these infections was 7.2/1000 patient-days (3.5/1000 patient-days for bacteriuria and 2.1/1000 patient-days for candidurias). Altogether, most patients were female (58.6%), with age of 55.9 years. They presented high scores for acute physiology (ASIS ≥4) and comorbidities (CHARLSON ≥3) with 74.6% and 54.5%, respectively. The average total hospital stay and diagnosis were prolonged, corresponding, respectively, to 15 days (SD ± 13.29) and 11 days (SD ± 12.52). In general, infections were mainly monocrobial (97.2%), with only 2.7% of polymicrobial etiology. Of the total 373 microorganisms, there was a predominance of Gram-negative bacilli (50.9%) identified in the following species in order: Escherichia coli (36.0%), Klebsiella pneumoniae (23.6%) and Acinetobacter baumannii (10.0%). Yeasts were responsible for 30.7% of the isolated, highlighting Candida albicans (57.0%). The frequency of strains characterized as multidrug-resistant was 62.4%. A positive correlation was observed between the use of polymyxin B (p= <0.0001), meropenem (p= 0.0063) and multidrug-resistant infections, showing that multidrug-resistant infections increased in proportion to the use of these antimicrobials. In the study cohort, 95/363 (26.1%) of the patients presented bloodstream infection (BSI) after the diagnosis of UTI, with 11.5% having the urinary tract as a probable focus of infection. Our results showed several significant differences in the comparison between bacteriuria and candiduria, the latter group had greater illness severity, were older, female sex, and showed a longer length stay (46.8% vs 62.3%, p= 0.0066), and evolution to death (28.1% vs. 55.0%, p= 0.0001). Conclusions- The observed cases of UTI were often caused by multidrug-resistant BGN associated with high epidemiological indicators. High mortality was associated with ICS acquired in the Unit, but there was an important association between secondary bacteremia and candidemia. These ICU-acquired candiduria might be associated with critical illness, longer ICU-LOS and poor prognosis.